Identifying research directions of a remotely-controlled merchant ship by revisiting her system-theoretic safety control structure. (September 2020) - Wróbel, Krzysztof; Gil, Mateusz; Montewka, Jakub
Highlights: System-theoretic safety control structure is revisited to identify research directions in the domain of autonomous shipping. 47 research papers are reviewed. Results indicate that most of scholars focus on the sharp-end of the system: its technological aspects. Abstract: Despite the concept of Maritime Autonomous Surface Ships (MASS) being in the limelight of research and development effort within the shipping industry, there are still some existing research gaps. These pertain not only to technical solutions to be implemented but also to the issue of the impact of new technology on maritime safety. In an attempt to identify these gaps, we perform a literature review of the operational features of remotely-controlled merchant vessels. The framework is based on a safety control structure developed in accordance with the principles of System-Theoretic Process Analysis (STPA). The results indicate that most scholars focus on the high-end components of the system, while some organizational and human-oriented issues remain under-explored. These results can be found relevant by scholars and industry partners active in the domain of autonomous shipping.